UZBEKISTAN'S EXPERIENCE IN ACHIEVING ECOLOGICAL SUSTAINABILITY: A COMPARATIVE ANALYSIS WITH INTERNATIONAL PRACTICE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article reviews the main strategies, programs and legislative initiatives implemented in the Republic of Uzbekistan to ensure environmental sustainability. It also analyzes Uzbekistan's achievements and current problems in this area, comparing them with international experience. The article assesses the directions of Uzbekistan's environmental policy based on the recommendations of international organizations.